1990
DOI: 10.1159/000281696
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-Enhanced Magnetic Resonance Imaging in the Staging of Urinary Bladder Neoplasms

Abstract: Magnetic resonance imaging (MRI) proved to be an important diagnostic tool in the correct staging of bladder neoplasms. The advantage of multiplane imaging and high soft-tissue contrast may be extended by the use of MRI contrast media such as the gadoliniumdiethylene-triaminepentaacetic acid complex. In 60 patients with suspected or proved bladder tumors, the results of preoperative gadolinium-enhanced MRI were correlated with the histopathologic findings. The staging accuracy of infiltrating tumors was 83% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…As clinical staging is not reliable for deeply infiltrative tumors, more accurate methods are needed. Recently, several investigators have described the use of Gdenhanced MR imaging for staging urinary bladder cancer (16,(23)(24)(25)(26). With the use of IV Gd-contrast, visualization of small tumors improved (16,(24)(25)(26), and furthermore, an increase in accuracy of local staging was reported (23,26).…”
Section: Bladder Cancermentioning
confidence: 99%
“…As clinical staging is not reliable for deeply infiltrative tumors, more accurate methods are needed. Recently, several investigators have described the use of Gdenhanced MR imaging for staging urinary bladder cancer (16,(23)(24)(25)(26). With the use of IV Gd-contrast, visualization of small tumors improved (16,(24)(25)(26), and furthermore, an increase in accuracy of local staging was reported (23,26).…”
Section: Bladder Cancermentioning
confidence: 99%
“…Although MR imaging is better than CT for staging urinary bladder cancer, CT is more commonly used in most centers be cause of its greater availability and of the greater familiarity with this tech nique. Recently, several authors have described the use of gadolinium-en hanced MR imaging for staging uri nary bladder cancer (10,(11)(12)(13)(14). With intravenously administered gadopentetate dimeglumine, visualization of small tumors improved (10,(12)(13)(14) and increased accuracy of local staging was reported (11,14).…”
Section: A R C In O M a Of The Urinary Bladdermentioning
confidence: 99%
“…Recently, several authors have described the use of gadolinium-en hanced MR imaging for staging uri nary bladder cancer (10,(11)(12)(13)(14). With intravenously administered gadopentetate dimeglumine, visualization of small tumors improved (10,(12)(13)(14) and increased accuracy of local staging was reported (11,14). The best stag ing results w ith contrast materialenhanced MR were obtained with fast Tl-w eighted imaging (9).…”
Section: A R C In O M a Of The Urinary Bladdermentioning
confidence: 99%
See 1 more Smart Citation
“…CT may only detect nodes of >1 cm and liver metastases of > 1.5 cm in diameter, and enlargement of the lymph nodes may not necessarily indicate metastatic disease [5]. Early studies showed that CT failed to detect nodal metastases in up to 40% of patients [6] and more recent imaging with MRI, including gadolinium‐DTPA‐enhanced images, produced similar results [7]. Even with the latest three‐dimensional MRI techniques the sensitivity of the detection of metastatic lymph nodes is still only 75% [8].…”
Section: Introductionmentioning
confidence: 99%